Integrated reporting: formation and evolutionary development - Mussipova, L.K.; Nakipova, G.N.; Kudaibergenova, S.K.; Zimakova, L.A. (BUKETOV BUSINESS REVIEW, 2019)
This article reviews theoretical aspects of integrated reporting, which poses as a new model of corporate reporting. It also establishes the essence of integrated reporting, identifies its pros and cons, and determines fundamental distinctions between traditional and integrated reporting. For this research following methods were used: systematic approach, generalization, comparison, analysis, and tracing cause and effect relationships. The goal of the integrated reporting preparation is studied in accordance with the International Integrated Reporting Standards. Research papers of foreign scholars regarding the questions of integrated reporting were used as a methodological groundwork of this research article. Along with this, the article presents a table where a comparative description of financial and integrated reporting is made, which makes it possible to reach a new level, providing users with better, reliable and reliable information. In the outcome, it was discovered that as soon as companies start the practice of using integrated reporting it will result in the higher trust of investors, which increases their investment attractiveness, what will have a positive impact on the state economy on its way to the world’s top 30 competitive countries.